STUDENTS’ PERCEPTION ON THE USE OF ENGLISH SONGS IN LEARNING LISTENING - Amalia, Nurul Ilmi; Jabu, Baso; Abduh, Amirullah (JTechLP: Journal of Technology in Language Pedagogy, 2023)
This study aims to determine students' perceptions on the use of English songs in learning listening for students of English Education, Universitas Negeri Makassar. The researcher applied mixed methods, namely quantitative and qualitative to achieve the objectives of the research. The data collected was in the form of a Likert questionnaire using the Google Form and interviews. The subjects of this study were students of the 2019 English Education Study Program. The sample from the questionnaire consisted of 40 students and interviews with 8 students who were taken using a voluntary sampling technique. The results of the data analysis show that: (1) Students’ perception on the use of English songs in learning Listening with a percentage of 55% of students are classified in the very positive category, 40% of students are classified as positive, 5% of students are classified as moderate, and no students have negative perceptions and very negative. (2) The results of the interviews show that students have a positive perception on the use of English songs in learning Listening.